Antimycobacterial activity of basic ethyl esters of alkoxy-substituted phenylcarbamic acids - Waisser, K; Drazková, K; Cizmárik, J; Kaustová, J (Folia microbiologica, 2003)
A series of 124 basic ethyl esters of alkoxy-substituted phenylcarbamic acids with the alkoxy group in position 2, 3 or 4 on the phenyl ring, and basic substituents attached to the ethyl moiety in position 2, were evaluated for in vitro antimycobacterial activity against strains of Mycobacterium tuberculosis, Mycobacterium kansasii and Mycobacterium avium. In vitro antimycobacterial activity becomes higher with increasing hydrophobic properties of the alkoxy groups. The p- and m-substituted derivatives were more active than the o-substituted ones. Direct relationship between the structure of the basic substituents and the activity was not found.
Keywords: Mycobacterium tuberculosis; Carbamates; karbamáty; Esters; Antitubercular Agents; Mycobacterium avium; estery; vztahy mezi strukturou a aktivitou; mikrobiální testy citlivosti; Microbial Sensitivity Tests; Structure-Activity Relationship; Mycobacterium; Mycobacterium kansasii; antituberkulotika